Hubungan Antara Kejadian Abortus Spontan dengan Kadar Hemoglobin di RSUD Dr. Moewardi - Sitorus, Andreas Peter; Melinawati, Eriana; Budiani, Dyah Ratna (Nexus Kedokteran Klinik, 2014)
Background : Many cases of abortions are caused by abnormal hemoglobin levels. World Health Organization (WHO) estimates that 35-75% of pregnant women in developing countries and 18% of pregnant women in developed countries undergo anemia while being pregnant. The purpose of this study is to determine the relationship between the incidence of spontaneous abortion with hemoglobin levels. Methods : This study is an analitic observational study with cross-sectional design. Its population are pregnant women who had been treated at the Obstetrics and Gynecology of Dr. Moewardi General Hospital. Subjects were taken with purposive random sampling technique. The data were collected using direct observation and subjectsâ medical records. Data were analyzed using Chi Square. Results : The results of this study found 40 subjects due to the case of this study. Subjects with anemia who did not experience abortion counted only 2 people (5.0%) and subjects who experienced abortion counted as many as 17 people (42.5%). While subjects with normal hemoglobin levels who did not experienced abortion aggregates to 18 people (45%) and subjects who experienced abortion counted as many as 3 people (7.5%). The calculation obtained p-value = 0.000 <0.05, and OR = 0.020, which means there is a relationship between the incidence of spontaneous abortion with hemoglobin levels. Conclusions : There is a significant relationship between the incidence of spontaneous abortion with hemoglobin levels. Low hemoglobin levels will increase the risk of abortion.Keywords: abortion, hemoglobin levels, anemiaÂ